Early Phenotype Programming in Birds by Temperature and Nutrition: A Mini-Review - Andrieux, Charlotte; Petit, Angélique; Collin, Anne; Houssier, Marianne; Métayer-Coustard, Sonia; Panserat, Stéphane; Pitel, Frédérique; Coustham, Vincent (Frontiers in Animal Science, 2022)
Early development is a critical period during which environmental influences can have a significant impact on the health, welfare, robustness and performance of livestock. In oviparous vertebrates, such as birds, embryonic development takes place entirely in the egg. This allows the effects of environmental cues to be studied directly on the developing embryo. Interestingly, beneficial effects have been identified in several studies, leading to innovative procedures to improve the phenotype of the animals in the long term. In this review, we discuss the effects of early temperature and dietary programming strategies that both show promising results, as well as their potential transgenerational effects. The timing, duration and intensity of these procedures are critical to ensure that they produce beneficial effects without affecting animal survival or final product quality. For example, cyclic increases in egg incubation temperature have been shown to improve temperature tolerance and promote muscular growth in chickens or fatty liver production in mule ducks. In ovo feeding has also been successfully used to enhance digestive tract maturation, optimize chick development and growth, and thus obtain higher quality chicks. In addition, changes in the nutritional availability of methyl donors, for example, was shown to influence offspring phenotype. The molecular mechanisms behind early phenotype programming are still under investigation and are probably epigenetic in nature as shown by recent work in chickens.